An optimized organic acid human sensory sourness analysis method. (23rd April 2021) - Mao, Yuezhong; Tian, Shiyi; Qin, Yumei; Cheng, Shiwen
Abstract: BACKGROUND: Sour taste perception builds on both chemical and physiological foundations, and plays an important role in food flavor, including that of fruit, beer, wine, and other beverages. A uniform sourness standard and sourness conversion method for researchers and food enterprises is necessary to obtain uniform conclusions. RESULTS: This study established an optimized organic acid sensory sourness analysis and sourness conversion method. It is based on sour sensory difference strength curves, which consist of an absolute threshold value and sensory difference threshold values. Defining the absolute threshold value of citric acid sourness as 1, sourness could be calculated according to the curve. With a logarithmic curve form, the acid sourness indexes (AI) were calculated as 1, 0.74, 0.77, 1.31, and 1.21 for citric, malic, fumaric, lactic, and tartaric acid samples, respectively. Consequently, each acid's sourness and concentration could be obtained and converted. Single acid and mixed acid sourness comparison evaluation's result implied that the novel method was more accurate (91.7–100%) than the hydrogen ion concentration method. CONCLUSION: The novel sourness determination and conversion equation would provide more accurate sourness standard and calculation method in food sensory areas. © 2021 Society of Chemical Industry.